Art marketing in the metaverse world: Evidence from South Korea - Seol Hwang; GeunWoo Koo (Cogent Social Sciences)
This study aims to describe the structural relationship between audience attitude and behavioral intention based on an audience’s experience value of a performance on a metaverse platform and their intention to accept this platform. A questionnaire was administered to the study sample audience who watched the performance on a metaverse platform at least once; we included 323 valid questionnaires in our final analysis. For the analysis, a structural equation model was performed to identify the above-mentioned relationship. Overall, the study findings demonstrate that aesthetic, which is the value of performing performances on a metaverse platform, had a major influence on performance viewing, and escapism significantly affected the use of a metaverse platform. Conversely, the educational experience of the audience did not appear significantly in the performance using the metaverse platform. Therefore, this study will be helpful in understanding how to utilize space and experience marketing functions in relation to metaverse performance and how to communicate in the future.